Unreduced Male Gamete Formation in Cymbidium and Its Use for Developing Sexual Polyploid Cultivars - Zeng, Rui-Zhen; Zhu, Jiao; Xu, Shi-Ying; Du, Guo-Hui; Guo, He-Rong; Chen, Jianjun; Zhang, Zhi-Sheng; Xie, Li (Frontiers in Plant Science, 2020)
Polyploidy plays important roles in crop improvement. Polyploid crops generally show increased organ size, improved buffering capacity for deleterious mutations, and enhanced heterozygosity and heterosis. Polyploidy can be induced artificially by antimitotic agents or occurs sexually through the production of unreduced gametes (2n gametes). Induced polyploidy has been widely used for improving crops, particularly floriculture crops. However, there are few reports of sexual occurring polyploids in floriculture crops. In the present study, we report the discovery of 2n gametes in an important orchid, Cymbidium and a reliable protocol established for selection of appropriate parents for 2n gamete production, ploidy level evaluation, in vitro culture of triploid progenies, and development of new polyploid cultivars. Cultivars developed from sexual polyploidization were more easily regenerated through rhizomes or protocorms, and regenerated seedlings had improved survival rate in a greenhouse. The sexual polyploid plants had compact growth style, produced fragrant flowers, and demonstrated heterosis in plant growth. Our results show that the use of 2n gametes is a viable way of improving Cymbidium.